METHODS TO TEACH HIGH SCHOOL STUDENTS ENGLISH THROUGH CONTENT AND LANGUAGE INTEGRATED LEARNING. (Лучшие интеллектуальные исследования, 2025)
Annotation: This article explores the implementation of Content and Language Integrated Learning (CLIL) as an effective approach to teaching English to high school students. By integrating subject content with language instruction, CLIL fosters both linguistic proficiency and academic knowledge. The article reviews relevant literature, outlines practical methods, presents results from case studies, discusses implications, and offers suggestions for educators to adopt CLIL effectively.